Los barrios de Arequipa: Crónica de una ciudad fragmentada - Zeballos Velarde, Carlos (2023)
This article seeks to understand the characteristics of the physical and social fragmentation of the city of Arequipa by exploring the historical evolution of its neighborhoods, which are fundamental elements of the city, both in their physical-spatial and socio-cultural configuration. The analysis of the structure of the neighborhoods, their configuration and transformation can contribute to understanding the dynamics and characteristics of the city. To this end, we explore the evolution of the pre-Hispanic, colonial and republican city from the generation of neighborhoods, and the implications that this had on the social divisions in Arequipa. It then discusses the role of urban planning since the second half of the twentieth century and how, on many occasions, it has emphasized dismemberment, fragmentation and marginality instead of being an agent of articulation. Finally, an urban renewal alternative is proposed that promotes social, urban and environmental integration in the periphery of Arequipa, through the development of a network of neighborhood centralities.